Mathematical creative thinking ability observed from student learning motivation in Jigsaw Cooperative Learning assisted by problem cards - Diani, Anisa Hayu; Dwijanto, Dwijanto (Unnes Journal of Mathematics Education, 2020)
The study aims to test the completeness Jigsaw cooperative learning assisted by problem cards for student’s mathematical creative thinking ability, to test the mathematical creative thinking abilities of students in Jigsaw cooperative learning assisted by problem cards compared with conventional learning, and analyze mathematical creative thinking abilities of students in Jigsaw cooperative learning assisted by problem cards observed from student’s learning motivation. The study uses mixed methods sequential explanatory design. Subjects in this study are six students of Junior High School in Semarang of class VIII B represent each group of learning motivation. Data collection methods used as follows: questionnaire, test, and interview. The result shows that: (1) student’s mathematical creative thinking ability in Jigsaw cooperative learning assisted by problem cards reaches learning completeness, (2) student’s mathematical creative thinking ability in Jigsaw cooperative learning assisted by problem cards higher than mathematical creative thinking ability in conventional learning, (3) student’s mathematical creative thinking ability observed from learning motivation are: (a) student with high learning motivation able to achieve all mathematical creative thinking ability indicators; (b) student with average learning motivation able to achieve fluency and elaboration indicators, but not achieve the flexibility and originality indicators; (c) student with low learning motivation less able to achieve fluency, flexibility, originality, and elaboration indicators.